NEW INEQUALITIES OF HERMITE-HADAMARD TYPE FOR FUNCTIONS WHOSE FIRST DERIVATIVES ABSOLUTE VALUES ARE s-CONVEX - Chen, Feixiang; Feng, Yuming (Italian Journal of Pure and Applied Mathematics, 2014)
In this paper, some new inequalities of the left-hand side of Hermite-Hadamard-type are obtained for functions whose first derivatives absolute values are s-convex.